Gender Bias In The Indonesian Language Textbook Grade VII - Yuliyanti, Putri Alifia; Muhyidin, Asep; Hadiansyah, Firman (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2025)
The Equality is the benchmark of justice, including in the context of education. Gender equality and social roles are aspects promoted in various policies, including the provision of inclusive teaching materials. This study aims to analyze gender representation in the Indonesian Language Textbook Grade VII Kurikulum Merdeka. The theoretical analysis is based on the concept of gender equality using a qualitative approach. Data are classified into two main categories: visual and textual. The data are then analyzed and grouped based on whether they support gender equality or contain elements of gender bias. The study results indicate that although gender equality and inclusive education are government programs, they are not yet fully reflected in the analyzed textbook. Significant gender bias is found both textually and visually. Visually, there are 137 representations of males compared to 100 representations of females, showing male dominance in illustrations. Textually, seven data points contain gender stereotypes. This study concludes that the Indonesian Language Textbook Grade VII Kurikulum Merdeka still contains significant gender bias, particularly in the visual aspect. These findings can serve as a foundation for developing more inclusive Indonesian language textbooks with a gender equality perspective in the future.